A Smart Cane Using GPS Device and GSM Module - Maha Khalil Ibrahim, Nadia Mahmood Hussien (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Blind have trouble living their life. They can't go anywhere alone. Blind people can use a smart stick to find their way around without having to ask anyone for help. It gives the person who is blind more confidence when they use this cane to help them walk. This device has an Arduino microcontroller, an ultrasonic and water sensors, an mp3 module, a buzzer, and a speaker. In order to see if there are things in front of the blind, an ultrasonic sensor is used to look at the reflection of ultrasonic waves from the things in front of the blind. Water sensor gives a signal ON, if there is a puddle in the way, you can find out before you get there. Use the MP3 module to tell people who can't see what they need to avoid. To be able to change how the sound comes out, you need to have an mp3. In order to communicate with each other, people use the GSM(Global System for Mobile Communications) system and the GPS system (global positioning system). A GPS tool helps the blind man get his location from satellites. GSM is used to send an alarm message to the blind family, telling them where he is. The system was written in the Arduino C programming language